2022
DOI: 10.3390/ph15020185
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of the Structure–Activity Relationship of a Lipophilic Nitroaromatic Prodrug Series Designed for Cancer Gene Therapy Applications

Abstract: PR-104A is a dual hypoxia/nitroreductase gene therapy prodrug by virtue of its ability to undergo either one- or two-electron reduction to its cytotoxic species. It has been evaluated extensively in pre-clinical GDEPT studies, yet off-target human aldo-keto reductase AKR1C3-mediated activation has limited its use. Re-evaluation of this chemical scaffold has previously identified SN29176 as an improved hypoxia-activated prodrug analogue of PR-104A that is free from AKR1C3 activation. However, optimization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…In contrast, under anoxic conditions (95% N 2 , 5% CO 2 ), a significant increase in cell death was observed across the analogue series, with LCK values ranging from 2.3 to 3.7. Unsurprisingly, LCK values were highest for the most lipophilic compounds ( 16 , 17 , and 20 ), consistent with our previous observations that increasing LogD 7.4 correlated with increasing LCK at tissuelike cell densities . Overall, these data indicated that all compounds in the dibromo and bromo/mesylate mustard analogue series were hypoxia-selective.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, under anoxic conditions (95% N 2 , 5% CO 2 ), a significant increase in cell death was observed across the analogue series, with LCK values ranging from 2.3 to 3.7. Unsurprisingly, LCK values were highest for the most lipophilic compounds ( 16 , 17 , and 20 ), consistent with our previous observations that increasing LogD 7.4 correlated with increasing LCK at tissuelike cell densities . Overall, these data indicated that all compounds in the dibromo and bromo/mesylate mustard analogue series were hypoxia-selective.…”
supporting
confidence: 90%
“…We recently reported a novel analogue of PR-104A, termed SN29176 ( 3 ) (Figure ), that was designed to be resistant to off-target activation by human AKR1C3 while retaining hypoxia selectivity in vitro and in vivo when administered as the pre-prodrug SN35141 ( 4 ) . In addition, we explored a series of analogues of SN29176 of varying lipophilicity and identified prodrug 5 (and its pre-prodrug 6 ) (Figure ) as a preferred hypoxia/GDEPT prodrug with an optimized bystander effect (the ability of cytotoxic metabolites to diffuse into and sterilize metabolically naïve neighboring cells) . While elimination of AKR1C3 activation is a significant advance, prodrugs 3 and 5 still contain an alcohol side chain and only achieve sufficient aqueous solubility for in vivo administration through use of a phosphate pre-prodrug strategy, rendering them susceptible to rapid clearance through the glucuronidation pathway.…”
mentioning
confidence: 99%
See 3 more Smart Citations